Study on Low-Temperature Catalytic Dehydrogenation Reaction of Tail Chlorine by Pd/Al2O3. (14th November 2016) - Wang, Hanhan; Lu, Tingting; Li, Yuna; Wu, Bo; Xue, Jianwei; Li, Fuxiang; Lv, Zhiping
Abstract : The catalytic dehydrogenation reaction of tail chlorine by Pd was studied using a fixed-bed reactor at low temperature from 30 to 100°C. Different catalyst supports such as SiO2 and Al2 O3 were applied to prepare Pd catalysts by the incipient-wetness impregnation method. And the catalysts were characterized by XRD, FTIR, XPS, SEM, and N2 adsorption-desorption. The catalyst Pd loading on both SiO2 and Al2 O3 had a catalytic effect on the dehydrogenation reaction, but the carrier Al2 O3 was more superior. The hydrogen conversion and selectivity of hydrogen-oxygen reaction increased first and then decreased with Pd loading amount and temperature by using Pd/Al2 O3 as catalysts, but the influence of temperature was limited when it was higher than 60°C. The hydrogen conversion was 97.38% and selectivity of hydrogen-oxygen reaction was 79% when the reaction temperature was at 60°C with 1 wt.% Pd/Al2 O3 .